1999
DOI: 10.1128/jcm.37.9.3055-3058.1999
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Group A Rotavirus, Human Calicivirus, Astrovirus, and Adenovirus Type 40 and 41 Infections among Children with Acute Gastroenteritis in Dijon, France

Abstract: Group A rotaviruses, human caliciviruses, astroviruses, and adenovirus types 40 and 41 were detected by enzyme immunoassay or reverse transcription-PCR in 61, 14, 6, and 3% of stool specimens from 414 children consulting for gastroenteritis between 1995 and 1998. These data highlight the importance of caliciviruses in infantile gastroenteritis. Among these, Norwalk-like viruses belonging to genogroup II were predominant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
68
4
19

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(108 citation statements)
references
References 25 publications
17
68
4
19
Order By: Relevance
“…A limited number of adenovirus strains have been associated with childhood diarrhea, types 40 and 41. Enteric adenovirus types 40/41 have been identified in up to 7.9% cases of diarrhea in children (Bon et al, 1999;Grimwood et al, 1995;Giordano et al, 2001;Qiao et al, 1999;Simpson et al, 2003). Human caliciviruses including norovirus and sapovirus are recognized as the main agents responsible for food-borne and nosocomial outbreaks of non-bacterial diarrhea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of adenovirus strains have been associated with childhood diarrhea, types 40 and 41. Enteric adenovirus types 40/41 have been identified in up to 7.9% cases of diarrhea in children (Bon et al, 1999;Grimwood et al, 1995;Giordano et al, 2001;Qiao et al, 1999;Simpson et al, 2003). Human caliciviruses including norovirus and sapovirus are recognized as the main agents responsible for food-borne and nosocomial outbreaks of non-bacterial diarrhea.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies investigating calicivirus in sporadic cases of gastroenteritis in children have concluded that caliciviruses comprise the second cause of viral diarrhea after rotavirus. (Bereciartu et al, 2002;Bon et al, 1999;Kirkwood and Bishop, 2001;Pang et al, 2000;Simpson et al, 2003;Subekti et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…NLVs have been implicated in 96% of the outbreaks of acute nonbacterial gastroenteritis in the US documented by the Centers for Disease Control and Prevention (CDC) between 1996(Fankhauser et al, 1998. Additionally, NLVs are a major cause of acute nonbacterial gastroenteritis in children and adults worldwide (Bon et al, 1999;Parks et al, 1999;Taylor et al, 1996;Vinje et al, 1997). NLV outbreaks have been reported in communities, schools and day care centers, nursing homes, hospitals, recreational areas, cruise ships, military ships and bases (Fankhauser et al, 1998;Grohmann et al, 1991;McCarthy et al, 2000;Sharp et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Estos virus son también una causa importante de GEA esporádica en los niños y ocupan, en la mayoría de las series, el segundo lugar en frecuencia después de los rotavirus 28 . En diversos trabajos se ha llegado a detectar norovirus en el 35% de los casos de GEA esporádica y en el 14% de los niños menores de 3 años hospitalizados por este motivo 29,30 . En España hay pocos datos epidemiológicos y de significación clínica en niños.…”
Section: Epidemiologíaunclassified